Enumeration and Categorization of the Indoor Plant of Bharatpur Metropolitan City - Acharya, Jamuna; K.L. Das, Manoj (BMC Journal of Scientific Research, 2024)
This study investigates indoor gardening practices in Bharatpur, Nepal. A combination of vision observations, online questionnaires, and a random selection of plant species were used to collect data. 41 respondents to the survey revealed a variety of indoor plants: 39% have less than five plants, 24.4% own ten or more, 19.5% own more than ten, and 17.1% own more than twenty. While 34.1% water their plants weekly, most participants (48.8%) water twice a week. Fertilizer is applied less regularly, with most people using it twice yearly (43.9%). Though gardeners face challenges such as dryness (41.5%) and insect infections (29.3%), indoor plants are recognized for their good energy (34.1%) and air purifying features (26.8%). Significant choices are available for specific plants, with the Epipremnum aureum coming in second at 31.7%, and the Dracaena trifasciata at 46.3% being the most popular. With a few of those received as gifts or online, nurseries consider 68.3% of plant purchases. The study identifies important plant families: Arecaceae, Asparagaceae, Asphodelaceae, Asteraceae, and Euphorbiaceae each have two to six species, while Araceae is the family with the greatest number with eleven. Just 1-2 species represent some families, such as Apocynaceae and Piperaceae.